6.3 Tobacco, Smoking Control and Health Education 2015
DOI: 10.1183/13993003.congress-2015.pa1883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking cessation on serum leptin and adiponectin levels

Abstract: Background: Evidence on the association of leptin and adiponectin and smoking is limited and discordant. Leptin and adiponectin represent the most abundant adipokines in human plasma that play crucial roles in the pathophysiology of metabolic syndrome, atherosclerosis and insulin resistance. Leptin up-regulates the expression of several pro-inflammatory cytokines and is increased upon weight gain. Adiponectin has been shown to possess insulin sensitizing, anti -inflammatory and anti-atherogenic properties and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…There are multiple studies implicating the rela-tionship between Leptin and smoking, but to the best of our knowledge, ours is the rst study assessing the e cacy of Leptin as a biomarker for smoking status from lymph node ne needle aspirates. Previous studies have demonstrated smoking cessation results in increased Leptin and Leptin could be a signi cant contributor to the correla-tion between smoking and body mass index (BMI) [14][15][16]. It has been suggested that elevated plasma Leptin following smoking cessation may be due to either increased Leptin secretion from adipose tissue or decreased removal of Leptin.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple studies implicating the rela-tionship between Leptin and smoking, but to the best of our knowledge, ours is the rst study assessing the e cacy of Leptin as a biomarker for smoking status from lymph node ne needle aspirates. Previous studies have demonstrated smoking cessation results in increased Leptin and Leptin could be a signi cant contributor to the correla-tion between smoking and body mass index (BMI) [14][15][16]. It has been suggested that elevated plasma Leptin following smoking cessation may be due to either increased Leptin secretion from adipose tissue or decreased removal of Leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some reports have linked leptin to tobacco craving and withdrawal-related symptoms. [19][20][21] Very few studies have examined leptin levels prospectively in accordance to the smoking habits in healthy individuals of both genders and in patients with COPD. In such a prospective study Lemieux A et al have found that leptin concentration en-hances during a period of 48 hours in females after quitting smoking, but remains stable in blood of non-smokers, in relapsers and in male abstainers.…”
Section: Discussionmentioning
confidence: 99%
“…19 Analogous results were reported by Kryfti M et al, who described an increase of serum leptin levels within a period of 3 months after smoking cessation and decreasing in the following 3 months (until month 6 after abstinence from smoking). 20 Reports have proven that smokers usually have a lower body weight compared to non-smokers. 21 Moreover, in most cases, smoking cessation is associated with weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking also a risk factor for metabolic syndrome, yet smoking cessation is also causing weight gain which lead to obesity and diabetes, but nicotine is associated to appetite control; hence, nicotine is used in weight loss research [8][9][10][11][12][13]. Other doubt raised from cardiovascular department, where smoking paradox is found.…”
Section: Introductionmentioning
confidence: 99%